2021
DOI: 10.1007/s40820-021-00777-2
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Interfacial Stability Via Absorption-Competition Mechanism for Long-Lifespan Zn Anode

Abstract: The stability of Zn anode in various Zn-based energy storage devices is the key problem to be solved. Herein, aromatic aldehyde additives are selected to modulate the interface reactions between the Zn anode and electrolyte. Through comprehensively considering electrochemical measurements, DFT calculations and FEA simulations, novel mechanisms of one kind of aromatic aldehyde, veratraldehyde in inhibiting Zn dendrite/by-products can be obtained. This additive prefers to absorb on the Zn surface than H2O molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…A comprehensive comparison by counting in both the current density, depositing capacity in one cycle and cumulative capacity was conducted. As demonstrated in SI Table S1, it can be observed that this strategy of utilizing HA additives possesses better cycling stability than most previous research via different modification methods. ,, , …”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A comprehensive comparison by counting in both the current density, depositing capacity in one cycle and cumulative capacity was conducted. As demonstrated in SI Table S1, it can be observed that this strategy of utilizing HA additives possesses better cycling stability than most previous research via different modification methods. ,, , …”
mentioning
confidence: 84%
“…To solve the above obstacles, abundant strategies toward bulk electrolyte systems and the electrode–electrolyte interface were proposed. Screening proper additives into the electrolyte environment has proven to be one of the most attractive solutions due to its properties of easy operation and multiple functions. Additives covering solute molecules and extra solvent usually can modulate the overall solvation structure environments, while some of them are capable of interacting with the surface of Zn anodes, together relieving the evolution of dendrite/byproducts. Among various additives, several organic polymer molecules have been introduced to achieve special effects. For instance, Pan’s group proposed poly­(ethylene oxide) (PEO) to manipulate the kinetics of Zn anodes by tuning the hydrogen bonding network in aqueous electrolytes, while stabilizing the electrode–electrolyte interface …”
mentioning
confidence: 99%
“…For Zn metal anode side, on one hand, the uneven deposition would lead to the rapid growth of Zn dendrite and produce the risk of puncturing the glass fiber (GF) separator [17,18]. Besides that, the side reactions especially for hydrogen evolution reaction (HER) would lead to a sharp increment of internal pressure in battery [19][20][21]. While for the vanadium oxide cathode side, from the perspective of storage mechanism, the co-embedding of Zn 2+ /H + into vanadium oxide host and accompanying with the generation of alkali by-product in the cathode/electrolyte interface is the most commonly acknowledged storage mechanism especially in the acidic electrolyte (Zn(OTf) 2 /H 2 O) system [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that Zn 2+ possesses a much lower binding energy with NAM (Figure S16 and Table S1), while the reshaped Zn 2+ solvation structure presents a decreased electrostatic potential (Figure e), both highlighting the modulating effect of NAM and coinciding with MD simulation results. Furthermore, compared to the original Zn 2+ -6H 2 O structure, the reshaped Zn 2+ -4H 2 O-NAM solvation shell also presents a smaller HOMO–LUMO gap and lower LUMO energy (Figure f), which suggest an enhanced Zn 2+ reduction activity …”
mentioning
confidence: 97%
“…Furthermore, compared to the original Zn 2+ -6H 2 O structure, the reshaped Zn 2+ -4H 2 O-NAM solvation shell also presents a smaller HOMO−LUMO gap and lower LUMO energy (Figure 3f), which suggest an enhanced Zn 2+ reduction activity. 33 For further probing the modulating essence of NAM on dendrite-free Zn growth on carbon fibers, scanning electron microscopy (SEM) tests were implemented. Figures 4a, S17, and S18 present successful detection of Zn, N, O, and C elements on the energy dispersive X-ray analysis (EDX) mapping of Zn plated carbon felt in ZnCl 2 -NAM electrolytes at different SOCs, indicating the adsorption of NAM on the zinc surface.…”
mentioning
confidence: 99%